THE DERIVATIVE OF SOME FUNCTIONS BY DEFINITION - Abdukakhhorov Izzatillo Shavkatali ogli (American Journals Publishing, 2025)
By taking the derivative of some complex function by definition, it is aimed at students to learn and creatively approach the derivative of a function.
Keywords: Derivative, Macleron number, function, definition, property, formula.